2022
DOI: 10.25165/j.ijabe.20221503.7367
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate control to increase productivity and nutritional quality of leafy vegetables in a cost-effective manner

Abstract: Food security is one of the key global challenges in this century. In Singapore, our research team has been using novel aeroponic technology to produce fresh vegetables since 1997. Aeroponic systems allow for year-round production of not only tropical, but also sub-tropical and temperate fresh vegetables, by simply cooling the roots suspended in aeroponic systems while the aerial parts grow under tropical ambient environments. It has also been used to investigate the impacts of root-zone CO 2 on vegetables by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…More and more studies have highlighted the importance of LED spectral quality on plants grown indoors [21][22][23][31][32][33][34]. However, the optimal LED spectral combinations vary depending on the plant species [26,30,35,36]. The success of indoor vertical farming illuminated by LEDs also hinges on local energy costs and environmental factors such as temperature, humidity, nutrient availability, and CO 2 levels [35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More and more studies have highlighted the importance of LED spectral quality on plants grown indoors [21][22][23][31][32][33][34]. However, the optimal LED spectral combinations vary depending on the plant species [26,30,35,36]. The success of indoor vertical farming illuminated by LEDs also hinges on local energy costs and environmental factors such as temperature, humidity, nutrient availability, and CO 2 levels [35].…”
Section: Introductionmentioning
confidence: 99%
“…However, the optimal LED spectral combinations vary depending on the plant species [26,30,35,36]. The success of indoor vertical farming illuminated by LEDs also hinges on local energy costs and environmental factors such as temperature, humidity, nutrient availability, and CO 2 levels [35]. Relying solely on energy-intensive indoor vertical farming, which necessitates controlled lighting and environmental conditions, is not sustainable for achieving the "30 by 30" goal, which emphasizes achieving more with fewer resources [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For vertical farming, most studies are using different combinations of LED light spectra at low PPFD between 150 to 300 µmol m -2 s -1 ( He et al., 2018 ; Palmer and van Iersel, 2020 ). It has been reported that photosynthetic performance, shoot and root biomass accumulation decreased in low light condition ( Yang et al., 2018 ; He and Qin, 2022 ). For instance, Yang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Using three different vegetables namely Kai Lan ( Brassica alboglabra ), Nai Bai ( B. chinensis L.) and mizuna ( B. juncea var. japonica) , we ( He and Qin, 2022 ) carried out comparative studies under different LED spectral qualities and quantities. All plants had much higher shoot fresh weight (FW) under a PPFD of 500 µmol m -2 s -1 than under a PPFD of 300 µmol m -2 s -1 regardless of LED combinations.…”
Section: Introductionmentioning
confidence: 99%